Comparative Review Between COVID-19 and Stunting: Communication Framework Toward Risk-Mitigating Behavior - Silva Liem; Rustono Farady Marta; Hana Panggabean; Clara R.P Ajisukmo (Faculty of Psychology Universitas Gadjah Mada, 2020)
In addition to COVID-19, stunting is another threat facing Indonesia. Although not as deadly as COVID-19, stunting requires immediate responses; otherwise it will burden our development agenda. Substantial evidences from application of Theory of Planned Behavior (TPB) accumulate significant relationship of health intentions to individuals’ behavior. Further extension of TPB that include other variables confirm the role of knowledge and risk perception in predicting health intentions and behavior. Similarly involve risk factors within public health area, risk communication of COVID-19 seems outperforms that of stunting. Using TPB’s perspective, this review of literature aims to analyze health promotion impacts of these health threats. Result indicates differences in risk communication strategy for COVID – indicated by emerging amateur health promoters – as to stunting. There is a need for intensive collaboration of Psychology and Communication studies in exploring communication strategies to help building health intentions toward performing risk-mitigating behaviors beyond COVID-19 and stunting alone.